Patients Undergoing Colorectal Cancer Screening Underestimate Their Cancer Risk and Delay Presentation for Screening. (2012) - Wang, Haili; Gies, Nicholas; Wong, Clarence; Sadowski, Dan; Moysey, Barbara; Fedorak, Richard N
Abstract : BACKGROUND: Colorectal cancer (CRC) is the third most common cancer in Canada. Screening guidelines recommend that first-time screening should occur at 50 years of age for average-risk individuals and at 40 years of age for those with a family history of CRC. OBJECTIVE: To examine whether persons with a positive CRC family history were achieving screening at 40 years of age and whether average-risk persons were achieving screening at 50 years of age. METHODS: The present study was a cross-sectional analysis of subjects who entered a colon cancer screening program and were undergoing CRC screening for the first time. RESULTS: A total of 778 individuals were enrolled in the present study: 340 (174 males) with no family history of CRC, and 438 (189 males) with a positive family history of CRC. For the group with a positive family history, the mean (± SD) age for primary screening was 54.4±8.5 years, compared with 58.2±6.4 years for the group with no family history. On average, those with a positive family history initiated screening 3.8 years (95% CI 2.8 to 4.8; P<0.05) earlier than those without. Adenoma polyp detection rate for the positive family history group was 20.8% (n=91) compared with 23.5 % (n=80) for the group with no family history. CONCLUSIONS: Individuals with a positive CRC family history are initiating screening approximately four years earlier than those without a family history; nevertheless, both groups are undergoing screening well past current guideline recommendations.